FIND THE DIFFERENCES” PICTURE AS MEDIA TO TEACH SPEAKING DESCRIPTIVE TEXT TO THE SEVENTH GRADERS (RETAIN, 2013)
Abstrak It is known that English is an international language which has been used by countries all over the world. Nowadays, many teachers agree that students should learn to speak English as a second language when interacting with others. It aims to make students capable of keeping track of where English is used by all walks of life and activities. A good teacher is a teacher who is able to create a fun learning environment, be a motivational speaker, and passion. In brief, English teacher should be creative in developing their teaching learning process to create good atmosphere, improve the students’ speaking skill, give attention to the speaking components. Studying English will be better with practicing speaking. To most people, mastering the art of speaking is the single most important aspect of learning a second or foreign language, and success is measured in terms of the ability to carry out a conversation in the language. There are many ways to teach speaking. Teaching speaking can be done through dialogues, pictures, games, etc. The teacher should choose a suitable way such as: using picture. There is a phrase that describes a picture means a thousand words. One of the alternative pictures in teaching speaking is using